Data filtering based stochastic gradient algorithms for multivariable CARAR-like systems - Wang, Dongqing; Shan, Tong; Ding, Rui (Mathematical Modelling and Analysis, 2013)
This paper considers identification problems for a multivariable controlled autoregressive system with autoregressive noises. A hierarchical generalized stochastic gradient algorithm and a filtering based hierarchical stochastic gradient algorithm are presented to estimate the parameter vectors and parameter matrix of such multivariable colored noise systems, by using the hierarchical identification principle. The simulation results show that the proposed hierarchical gradient estimation algorithms are effective.